Islamic Religious Values in Sapta Tirta Pablengan Folklore - Istiana, Rahayu Nur; Rakhmawati, Ani; Wardani, Nugraheni Eko (el Harakah: Jurnal Budaya Islam, 2021)
“Sapta Tirta Pablengan” folklore which is originated from Karanganyar Regency, Central Java, is one of Javanese identities with a lot of local values and wisdom. This study aims to describe and explain Islamic religious values behind “Sapta Tirta Pablengan” folklore. It is a descriptive qualitative research with content analysis method. The data were collected through literature study, structured and in-depth interviews, and field observations. The data analysis employed independent techniques and flow analysis techniques. The results of the study show that the Islamic religious values of Sapta Tirta Pablengan folklore could be grouped into three dimensions along with their respective indicators. The first is faith dimension with indicators: (1) believing in Allah, (2) believing in His destiny, (3) surrendering to Him, (4) sincere, and (5) practicing worship. The second is experience dimension with indicators: (1) helpful, (2) honest, (3) forgiving, and (4) hard work. The third category is natural dimension with the indicator of managing and conserving nature. Therefore, “Sapta Tirta Pablengan” folklore can be recommended a learning material at schools because it contains Islamic religious character education. Cerita rakyat “Sapta Tirta Pablengan” yang berasal dari Kabupaten Karanganyar, Jawa Tengah, merupakan salah satu jati diri masyarakat Jawa yang sarat akan nilai-nilai dan kearifan lokal.  Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan nilai religius Islam yang terkandung dalam cerita rakyat “Sapta Tirta Pablengan.” Jenis penelitian ini adalah deskriptif kualitatif dengan metode analisis isi. Metode pengumpulan data dengan studi pustaka, wawancara terstruktur dan mendalam, serta observasi lapangan. Teknik analisis data menggunakan teknik mandiri dan teknik analisis mengalir.  Hasil kajian menunjukkan mengandung nilai religius Islam dikelompokkan menjadi tiga dimensi beserta indikator yang menyertai. Pertama, dimensi keyakinan dengan indikator: (1) percaya adanya Allah, (2) percaya pada takdir Allah, (3) pasrah pada Allah, (4) iklhas, dan (5) menjalankan ibadah. Kedua, dimensi pengalaman dengan indikator: (1) suka menolong, (2) jujur, (3) pemaaf, dan (4) kerja keras. Ketiga, dimensi alam dengan indikator mengelola dan melestarikan kekayaan alam. Dengan demikian, cerita rakyat “Sapta Tirta Pablengan” bisa direkomendasikan sebagai materi pembelajaran sastra di sekolah karena sarat dengan pendidikan karakter religius.